Technological innovation and engineering practice of damage reduction mining and ecosystem restoration in open-pit coal mine - Quansheng Li; Xiaobin Li (Global Sustainability)
Abstract Non-technical summary To address the issues of declining groundwater levels and the degradation of soil ecological functions caused by open-pit coal mining in China. Based on theoretical analysis, laboratory experiments, on-site monitoring, mathematical modeling, and other means, the concept of coal ecological protection mining of ‘damage reduction mining, three-dimensional protection, systematic restoration’ is proposed. The mining concept has achieved remarkable ecological restoration effects, leading the scientific and technological progress of safe, efficient and green mining in open-pit coal mines.